Beyond language proficiency: integrating soft skills into Business English teaching - Nernere, Maria Setyaningsih (Universitas Merdeka Malang, 2024)
Teaching Business English extends beyond mastering vocabulary and grammar; it equips learners with the skills to communicate effectively in professional environ-ments. In busines world, soft skills such as communication, teamwork, problem-solving, and negotiation are equally important as linguistic proficiency. This articleexamines effective methodologies for integrating soft skills into Business Englishteaching by reviewing relevant literature and case studies published between 2019and 2024. The findings highlight the urgency of incorporating soft skills into thecurriculum to enhance learners’ ability to navigate real-world business contexts.Several practical methodologies, such as project-based learning, role-playing, andcase study analysis, are recommended to support this integration. This discussionprovides valuable insights for curriculum designers, educators, and learners, help-ing them optimize their roles in fostering comprehensive Business English educa-tion.